The pathogenesis of thyroid autoimmune diseases: New T lymphocytes – Cytokines circuits beyond the Th1−Th2 paradigm. Issue 3 (24th September 2018) - Li, Qian; Wang, Bin; Mu, Kaida; Zhang, Jin‐An
Abstract: Autoimmune thyroid disease (AITD) is one of the most common organ‐specific autoimmune disorders. It mainly manifests as Hashimoto's thyroiditis (HT) and Graves' disease (GD). HT is characteristic of hypothyroidism resulting from the destruction of the thyroid while GD is characteristic of hyperthyroidism due to excessive production of thyroid hormone induced by thyrotropin receptor‐specific stimulatory autoantibodies. T lymphocytes and their secretory cytokines play indispensable roles in modulating immune responses, but their roles are often complex and full of interactions among distinct components of the immune system. Dysfunction of these T cells or aberrant expressions of these cytokines can cause the breakdown of immune tolerance and result in aberrant immune responses during the development of AITDs. This review summarizes recently identified T subsets and related cytokines and their roles in the pathogenesis of AITDs with the hope to provide a better understanding of the precise roles of notably identified T subsets in AITDs and facilitate the discovery of functional molecules or novel immune therapeutic targets for AITDs. Abstract : Beyond the Th1−Th2 paradigm, newly discovered T lymphocytes and their special cytokines play indispensable roles in modulating immune responses, but their roles are often complex. Dysfunction of these T cells or aberrant expressions of these cytokines can cause the breakdown of immune tolerance and result in aberrant immune responses during the development of autoimmune thyroid diseases.